2010
DOI: 10.2165/11538410-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence of Sitagliptin/Metformin Fixed-Dose Combination Tablets and Concomitant Administration of Sitagliptin and Metformin in Healthy Adult Subjects

Abstract: The sitagliptin/metformin 50 mg/500 mg and 50 mg/1000 mg FDC tablets are bioequivalent to co-administration of corresponding doses of sitagliptin and metformin as individual tablets and support bioequivalence to the sitagliptin/metformin 50 mg/850 mg tablet strength. These results indicate that the safety and efficacy profile of co-administration of sitagliptin and metformin can be extended to the sitagliptin/metformin FDC tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…On the basis of the ideal efficacy of DPP‐4 inhibitors and metformin combination therapy, pharmaceutical companies have developed a fixed‐dose combination (FDC) of the two classes of antidiabetic drugs. Bioequivalence studies have shown that the bioequivalence, safety and efficacy profile of co‐administration of DPP‐4 inhibitors and metformin can be extended to the FDC and extended‐release FDC tablets . The changes from baseline HbA1c and FPG were greater in patients treated with the DPP‐4 inhibitors/metformin FDC than in those treated with metformin monotherapy .…”
Section: Efficacy and Safety Of Dpp‐4 Inhibitors And Metformin Combinmentioning
confidence: 99%
“…On the basis of the ideal efficacy of DPP‐4 inhibitors and metformin combination therapy, pharmaceutical companies have developed a fixed‐dose combination (FDC) of the two classes of antidiabetic drugs. Bioequivalence studies have shown that the bioequivalence, safety and efficacy profile of co‐administration of DPP‐4 inhibitors and metformin can be extended to the FDC and extended‐release FDC tablets . The changes from baseline HbA1c and FPG were greater in patients treated with the DPP‐4 inhibitors/metformin FDC than in those treated with metformin monotherapy .…”
Section: Efficacy and Safety Of Dpp‐4 Inhibitors And Metformin Combinmentioning
confidence: 99%
“…Two randomized, open-label studies conducted by Chang et al 33 and Migoya et al 34 in the years 2012 and 2010 states that FDCs of dapagliflozin and metformin and of sitagliptin and metformin are bioequivalent to the concomitant doses administered as individual components.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some limitations for FDCs such as difficulty in dose titration and stability problems between the drugs leading to incompatibilities. Study design, intervention, outcomes, and safety of FDC use in T2DM was shown in Table II,3, 5, 10, 12, 14, 16, 18, 23, 30, 31 and bioavailability of FDCs is shown in Table III 33, 34Table IIStudies reporting the use of FDCs in T2DM patients.AuthorType of studyInterventionOutcomesSafetyVed et al 3 (2016)N = 400, open label, prospective, nonrandomized, multicenter, observational study, 3 monthsVildagliptin (50 mg) + metformin (500, 850, 1000 mg) as FDCMean value for FBG, PPG, and HbA 1c were significantly reduced after treatmentNot reported in this studyRombopoulos et al 18 (2014)N = 366, multicenter, observational study, 26 weeksVildagliptin (50 mg) + metformin (850 mg) as FDCIt resulted in a greater reduction in HbA 1c compared with free-dose combination; the patients with FDC were more compliant than with free doseNot reported in this studyLewin et al 23 (2013)N = 273, phase III, randomized, double- blind, parallel group, 52 weeksEmpagliflozin (25, 10 mg) + linagliptin (5 mg) as FDCReduction in HbA 1c was significantly greater with FDC compared with individual componentsThe incidence of ADRs such as UTI, genital infection, were more with empagliflozin 25 mg + linagliptin 10 mg compared with the other compared with the other group but were tolerable with medicationWang et al 5 (2012)N = 233, randomized, double-blind, parallel group, 16 weeksAcarbose (50 mg) + metformin (500 mg) TDS as FDCThe combination significantly reduced FBS, HbA 1c , and PPPG with superior efficacy compared with monotherapyNo hypoglycemia was reported.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized, open-label, 2-part, 2-period crossover study, bioequivalence between FDC and coadministration of corresponding doses of sitagliptin and metformin was established in 48 nondiabetic subjects supporting the efficacy and safety of fixed dose combination treatment. 46 In a placebo-controlled, multipledose, crossover trial in 13 patients with type 2 diabetes, steady state pharmacokinetics of sitagliptin and metformin were not altered by their coadministration, and no drug-related adverse effects were reported. 47 Currently, there are no trials comparing the effect of FDC of sitagliptin and metformin on patient compliance although it might be expected that treatment with an FDC could improve patient compliance compared with treatment with separate agents.…”
Section: Pharmacokinetic and Pharmacodynamic Profile And Adverse Drugmentioning
confidence: 98%
“…FDC tablets are available in doses of 50 mg sitagliptin + 500 mg metformin or 50 mg sitagliptin + 1000 mg metformin. In a randomized, open-label, 2-part, 2-period crossover study, bioequivalence between FDC and coadministration of corresponding doses of sitagliptin and metformin was established in 48 nondiabetic subjects supporting the efficacy and safety of fixed dose combination treatment 46. In a placebo-controlled, multipledose, crossover trial in 13 patients with type 2 diabetes, steady state pharmacokinetics of sitagliptin and metformin were not altered by their coadministration, and no drug-related adverse effects were reported 47.…”
Section: Pharmacokinetic and Pharmacodynamic Profile And Adverse Drugmentioning
confidence: 99%